Crystallographic identification of Eu@C2n (2n = 88, 86 and 84): completing a transformation map for existing metallofullerenes. Issue 7 (21st December 2018) - Bao, Lipiao; Yu, Pengyuan; Pan, Changwang; Shen, Wangqiang; Lu, Xing
Abstract : A transformation map covering as many as 98% of metallofullerenes with clear C2 n (2 n = 74–86) cage structures is uncovered with C 2 (27)-C88, C 1 (7)-C86, C 2 (13)-C84 and C 2 (11)-C84 as key links. Abstract : Revealing the transformation routes among existing fullerene isomers is key to understanding the formation mechanism of fullerenes which is still unclear now because of the absence of typical key links. Herein, we have crystallographically identified four new fullerene cages, namely, C 2 (27)-C88, C 1 (7)-C86, C 2 (13)-C84 and C 2 (11)-C84, in the form of Eu@C2 n, which are important links to complete a transformation map that contains as many as 98% (176 compounds in total) of the reported metallofullerenes with clear cage structures (C2 n, 2 n = 86–74). Importantly, the mutual transformations between the metallofullerene isomers included in the map require only one or two well-established steps (Stone–Wales transformation and/or C2 insertion/extrusion). Moreover, structural analysis demonstrates that the unique C 2 (27)-C88 cage may serve as a key point in the map and is directly transformable from a graphene fragment. Thus, our work provides important insights into the formation mechanism of fullerenes.